Opioid receptors: drivers to addiction? - Darcq, Emmanuel; Kieffer, Brigitte Lina (Nature reviews. Neuroscience, 2018)
Drug addiction is a worldwide societal problem and public health burden, and results from recreational drug use that develops into a complex brain disorder. The opioid system, one of the first discovered neuropeptide systems in the history of neuroscience, is central to addiction. Recently, opioid receptors have been propelled back on stage by the rising opioid epidemics, revolutions in G protein-coupled receptor research and fascinating developments in basic neuroscience. This Review discusses rapidly advancing research into the role of opioid receptors in addiction, and addresses the key questions of whether we can kill pain without addiction using mu-opioid-receptor-targeting opiates, how mu- and kappa-opioid receptors operate within the neurocircuitry of addiction and whether we can bridge human and animal opioid research in the field of drug abuse.